USING INSTRUCTIONAL MEDIA IN TEACHING ENGLISH FOR YOUNG LEARNERS (EYL) IN SOUTHWEST PAPUA - Sari, Sari; Baa, Sultan (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The objectives of the research were to find out the types of instructional media used by teachers to teach English for young learners, to explore the teachers’ strategies in using those media, and to discover the students' perceptions about instructional media application in their classes. This research used a qualitative case study design with the triangulation analysis method. The participants of this research were English teachers and students of SDIT Alizzah Sorong, Southwest Papua. Data collection was carried out through classroom observation, semi-structured interviews and documentation. The results of the research showed that: (1). The types of instructional media used by English teachers were (a) Audio, such as: Song., (b) Visual, such as: Realia, Picture, Course Book, and Board; and (c) Audio Visual, such as: Computer Based Technology and videos; (2). When using instructional media, teachers used three different strategies in three different stages: (a) Preparation; having routine activities in creating instructional media called KKG (Kelompok Kerja Guru), paying attention to the suitability of the material and student characteristics, and paying attention to the costs incurred in creating instructional media (b) Classroom implementation: using teaching methods such as paying attention to students' seating positions and the situation in the classroom during the learning process. (c) Evaluation; evaluating instructional media together with co-teachers in KKG activities and by giving tests to students. Detailed findings will be presented and their implications discussed.